2019
DOI: 10.1002/cam4.2382
|View full text |Cite
|
Sign up to set email alerts
|

Developing a prediction model for disease‐free survival from upper urinary tract urothelial carcinoma in the Korean population

Abstract: Background In this study, we aimed to propose a validated prediction model for disease‐free survival (DFS) after radical nephroureterectomy (RNU) in a Korean population with upper urinary tract urothelial carcinoma (UTUC). Methods We performed a retrospective review of 1561 cases of UTUC who underwent either open RNU (ONU, n = 906) or laparoscopic RNU (LNU, n = 615) from five tertiary Korean institutions between January 2000 and December 2012. Data were used to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…The overall 5‐year overall survival probability in Taiwan is comparable with those reported in Western countries and Japan, 3,22,23 and is better than those reported in Australia 5 . Tumor stage and age have been considered as key determinants in explaining the difference of UTUC outcomes within one country 24,25 . Although patients with UTUC in Taiwan and China were significantly younger, typically female, and had a lower tumor stage than those in Japan and the USA, previous studies found similar prognoses between these countries, suggesting that international UTUC treatments and care are of comparable quality 23,26 .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The overall 5‐year overall survival probability in Taiwan is comparable with those reported in Western countries and Japan, 3,22,23 and is better than those reported in Australia 5 . Tumor stage and age have been considered as key determinants in explaining the difference of UTUC outcomes within one country 24,25 . Although patients with UTUC in Taiwan and China were significantly younger, typically female, and had a lower tumor stage than those in Japan and the USA, previous studies found similar prognoses between these countries, suggesting that international UTUC treatments and care are of comparable quality 23,26 .…”
Section: Discussionmentioning
confidence: 65%
“… 5 Tumor stage and age have been considered as key determinants in explaining the difference of UTUC outcomes within one country. 24 , 25 Although patients with UTUC in Taiwan and China were significantly younger, typically female, and had a lower tumor stage than those in Japan and the USA, previous studies found similar prognoses between these countries, suggesting that international UTUC treatments and care are of comparable quality. 23 , 26 In contrast to the findings of the present systematic review, men had a poorer overall survival rate, possibly because women with UTUC in Taiwan are healthier compared with those in other countries due to unique causes.…”
Section: Discussionmentioning
confidence: 99%